Praderas higrófilas de Deschampsion mediae en el subsector Torcalense (sector Antequerano, Málaga, España). - Pérez-Latorre, Andrés V.; Casimiro Soriguer-Solanas, Federico; Cabezudo, Baltasar (Acta Botanica Malacitana, 2014)
Wet meadows of Deschampsion mediae in the Torcal mountain range (Antequerano phytogeographical sector, Malaga, Spain) Palabras clave. Vegetación, flora, humedales, cordillera del Torcal, Andalucía Key words. Vegetation, flora, wetlands, Torcal mountain range, Andalusia